The Important Role of Influencer Content in Increasing Interest in Visiting Gelora Karno Stadium - Pradini, Gagih; Anggrayni, Fellysha; Awaloedin, Dipa Teruna (International Journal of Education, Information Technology, and Others, 2024)
Gelora Karno Stadium (GBK) is one of the international stadiums in Indonesia that is not only used for sports and entertainment events, but also attracts tourists who are interested in its history and activities. In an effort to promote the stadium as a tourist destination, the use of social media and collaboration with influencers has become an increasingly popular strategy. This research explores the role of influencers in the promotion of tourist destinations, especially in the context of Gelora Karno Stadium. Through SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis, this study assesses the advantages and disadvantages of using influencers in promotional strategies, as well as opportunities and threats that may arise. The results of the analysis show that influencers have a wide reach and can create creative content that appeals to the audience, so as to increase the attractiveness of tourist destinations. However, reliance on certain influencers can be a risk if they are involved in controversy or social media trends change. Collaborations with leading influencers provide opportunities to increase public exposure and trust in travel destinations, but high costs and changes in social media algorithms can be threats to promotional success. This research concludes that the synergy between public relations (PR) strategies and the role of influencers is the key to success in promoting tourist destinations. An effective PR strategy provides a strong foundation by creating a positive story about the destination, while influencers offer a personal dimension that is able to reach the audience in a more authentic way. With the right selection of influencers and a mature strategy, Gelora Karno Stadium can harness the power of social media to attract tourists and improve the image of the destination. Effective synergy between PR strategies and influencers will ensure successful promotion and attract significant visits to Gelora Karno Stadium.